Comparison of Blood Gas Analysis on Hemodialysis in Patients with Chronic Kidney Diseases - Nenden Senina Rindaha; Sulina Yanti Wibawa; Yuyun Widaningsih; Rachmawati A. Muhiddin (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Chronic Kidney Disease (CKD) is defined as a renal failure that has lasted for more than three months. Hemodialysis is the type of kidney replacement therapy that is mostly used, and blood gas analysis can be used to identify this condition. This study is to compare the blood gas analysis on pre-and post-dialysis in patients with CKD using pH, PaCO , PaO , HCO , SO , 2 2 3 2 and BE as markers of improvement in the patients'condition. The population was all patients diagnosed with CKD and hemodialysis at Dr. Wahidin Sudirohusodo Hospital, and eligible according to the criteria in this study. The sample size was determined using Federer's calculation, and the statistical analysis using paired T-test and Wilcoxon signed-rank test with Î±=0.05. Subjects were 34 patients, consisting of 18 females (52.9%) and 16 males (47.1%). Hemodialysis had the most significant impact on the PaO and SaO variables. Relation between PaO and SaO was illustrated in a sigmoid curve. 2 2 2 2 Oxygen-bound hemoglobin increased after the first molecule was bound. An almost full PaO pressure will cause a slight 2 increase in SaO. Whereas at <90% saturation, a slight decrease in PaO will cause a large decrease in SaO . PaO and SaO 2 2 2 2 2 determine cardiac efficiency and the markers for assessing the metabolic conditions of the lungs and heart that correlate with oxygen. Chronic kidney disease patients experienced improved conditions after undergoing hemodialysis with increased blood gas values, especially in PaO and SaO.